2015
DOI: 10.1016/j.icarus.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mapping of surface physical properties of Mars from CRISM multi-angular data: Application to Gusev Crater and Meridiani Planum

Abstract: The analysis of particle physical properties (grain size, shape and internal structure) and its organization (surface porosity, roughness, and grain size distribution) provides information about the geological processes which formed and modified planetary surfaces. CRISM (Compact Reconnaissance Imaging Spectrometer for Mars) multi-angular observations (varied emission angles) allow for the characterization of the surface scattering behavior, which depends on the composition and on the material physical propert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…To quantify the evolution of the photometric behavior of each sample with the wavelength, we used the procedure developed by Fernando et al (2013Fernando et al ( , 2015 using the fast implementation strategy of Schmidt and Fernando (2015). This methodology uses a Bayesian approach to estimate photometric parameters from the Hapke model (Hapke, 1993).…”
Section: Inversion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify the evolution of the photometric behavior of each sample with the wavelength, we used the procedure developed by Fernando et al (2013Fernando et al ( , 2015 using the fast implementation strategy of Schmidt and Fernando (2015). This methodology uses a Bayesian approach to estimate photometric parameters from the Hapke model (Hapke, 1993).…”
Section: Inversion Methodsmentioning
confidence: 99%
“…Helfenstein and Veverka, 1989;Helfenstein et al, 1994Helfenstein et al, , 1996Domingue et al, 2002;Newburn et al, 2003;Hillier et al, 2011) and planets (e.g. Veverka et al, 1988;Johnson et al, 2006a,b;Jehl et al, 2008;Fernando et al, 2013Fernando et al, , 2015 have been studied. These photometric studies are generally performed at one or a couple of wavelengths in the visible and/or very near-IR.…”
Section: Introductionmentioning
confidence: 99%
“…Their study has found that w, b, c andθ follow a unimodal distribution around the solution and the parameters can be described with a mean and standard deviation when uncertainties are lower than about 5%. Fernando et al (2015a) state that a phase angles > 90 • and phase angle coverage > 50 • are required to constrain the degeneracy, which is, in fact, satisfied by the OSIRIS data in Baetica region. Since it is not the scope of the work to test once more the validity of the Hapke parameters, we have taken Fernando et al results into consideration when developing our inversion procedure.…”
Section: H(x W)mentioning
confidence: 98%
“…In the case of the Hapke model, the entangling of its parameters, mainly the w, g sca andθ , have been widely criticized for a few decades (Helfenstein and Veverka, 1989). Nevertheless Fernando et al (2013), Fernando et al (2015a) and Schmidt and Fernando (2015) have recently applied a Bayesian inversion to study the probabilistic density function of each Hapke parameter and their degeneracy. Their study has found that w, b, c andθ follow a unimodal distribution around the solution and the parameters can be described with a mean and standard deviation when uncertainties are lower than about 5%.…”
Section: H(x W)mentioning
confidence: 99%
“…We test the BRDF observation, sampled 48 times at 2 incidence angles 40 (Jehl et al, 2008;Fernando et al, 2013;Fernando et al, 2015).…”
Section: Full Brdfmentioning
confidence: 99%